A concorrência em regime assimétrico no marco regulatório dos portos: o caso dos terminais de contêineres de Itajaí e Navegantes - Jucá, Paulo Renato (2019)
This work intends to discuss the regulatory framework for the port sector established by Law no. 12,815/2013. This work will focus on the changes introduced by the regulatory framework on the ways in which ports are explored and their impact on the competition between private operators subject to different legal regimes (regulatory asymmetry). In order to stimulate competition, the regulatory framework modifies the criteria for distinguishing port operators. With Law no. 12,815/2013, private operators of port terminals are no longer differentiated by the criterion of cargo ownership and are now distinguished by the geographical criterion. Unrestricted competition for cargo handling between public terminals and private use terminals (TUPs) is now allowed. This dissertation intends to contribute to the understanding of the effects of this direct competition between port operators subject to asymmetric regulation — through the case study of the public terminal located in Itajaí (operated by APM Terminals Itajaí S.A.) and the private terminal installed in Navegantes (operated by Portonave S.A.), both located in the State of Santa Catarina.